Reminiscência e memória no ensaio fotográfico “Banheiro de Frida Kahlo” de Graciele Iturbide - Coterno, Fábio Luiz (2023)
This research aims to present the spaces of memory and intermediality in Graciela Iturbide's photography in the essay El baño de Frida Kahlo, which portrays Frida Kahlo's personal objects have been kept in a bathroom as a reliquary for 50 years. Based on bibliographic studies, the photography regarding the artist's personal belongings is exhibited as a space between two women of substantial importance for art, politics, and women's emancipation in Latin America. This research is based on the assumption that a photograph becomes a new reference for the position adopted by the original work and how it can be reinterpreted by the author's memory. Walter Benjamin studied aura in photography as some divine condition, the power wielded by the image according to Roland Barthes' concept of punctum, and Georges Didi-Huberman's notion of this is, this was when he analyzes the image that returns to the spectator. These theoretical bases have helped them to understand how the photographs in this essay converge to a new meaning, full of memories as a "footprint and a scar" go along with perpetuation of live, as it was pointed out by Jeanne Marie Gagnebin. Graciela Iturbide's photos, with their reinterpreted possibilities, point us towards a new life and a new art for Frida Kahlo's memory, as guardians of a temple, as suggested by Aleida Assmann, without neglecting the idea of photography as a real time frame, proposed by Phillippe Dubois. He understood photography as a memory and history way from Boris Kossoy's perspective and discussed about photography as contemporary art according to André Rouillé's conception